Interleukin-6 Promotes Murine Estrogen Deficiency-Associated Cerebral Aneurysm Rupture. Issue 4 (2nd July 2019) - Wajima, Daisuke; Hourani, Siham; Dodd, William; Patel, Devan; Jones, Chad; Motwani, Kartik; Fazal, Hanain Z; Hosaka, Koji; Hoh, Brian L
Abstract: BACKGROUND: Estrogen deficiency is associated with cerebral aneurysm rupture, but the precise mechanism is unknown. OBJECTIVE: To test the hypothesis that IL-6 is required for the increase in aneurysm rupture rate observed in estrogen-deficient mice. METHODS: We analyzed IL-6 expression in human cerebral aneurysms. We induced cerebral aneurysms in estrogen-deficient female C57BL/6 mice that had undergone 4-vinylcyclohexene diepoxide (VCD) treatment or bilateral ovariectomy (OVE). Mice were blindly randomized to selective IL-6 inhibition (IL-6 receptor [IL-6R] neutralizing antibody, n = 25) or control (isotype-matched IgG, n = 28). Murine cerebral arteries at the circle of Willis were assessed for aneurysm rupture and macrophage infiltration. RESULTS: IL-6 is expressed in human cerebral aneurysms, but not in control arteries. Serum IL-6 is elevated in ovariectomized female mice compared to sham control (14.3 ± 1.7 pg/mL vs 7.4 ± 1.5 pg/mL, P  = .008). Selective IL-6R inhibition suppressed cerebral aneurysm rupture in estrogen-deficient mice compared with control (VCD: 31.6% vs 70.0%, P  = .026; OVE: 28.6% vs 65.2%, P  = .019). IL-6R inhibition had no effect on formation or rupture rate in wild-type mice. IL-6R neutralizing antibody significantly reduced macrophage infiltration at the circle of Willis (1.9 ± 0.2 vs 5.7 ± 0.6 cells/2500 μm 2 ; n = 8 vs n = 15; P  < .001). CONCLUSION: IL-6 is increased in the serum of estrogen-deficient mice and appears to play a role in promoting murine estrogen deficiency-associated cerebral aneurysm rupture via enhanced macrophage infiltration at the circle of Willis. Inhibition of IL-6 signaling via IL-6 receptor neutralizing antibody inhibits aneurysm rupture in estrogen-deficient mice. IL-6 receptor inhibition had no effect on aneurysm formation or rupture in wild-type animals.